Analytical Solution to a Class of Truly Nonlinear Oscillators - Alvaro H. Salas S. (Research Updates in Mathematics and Computer Science Vol. 4, 2024)
We introduce new techniques for solving truly nonlinear oscillators. We give approximate expressions for their period. Using this period we find approximate analytical solutions using both trigonometric and jacobian functions. The results are illustrated with concrete examples.